1996
DOI: 10.1006/jaut.1996.0046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Insulin Treatment on the Number of ER-MP23+Macrophages in the Pancreas of NOD Mice. Is the Prevention of Diabetes Based on β-cell Rest?

Abstract: Prophylactic insulin treatment has been shown to have beneficial effects in type 1 diabetes, both in humans and in various animal models of the disease. In experimental models, the protective effect of prophylactic insulin treatment was observed in two parameters: (1) progression of insulitis and (2) diabetes incidence. The mechanism of protection still remains to be investigated. We therefore analysed by immunohistochemistry the effect of prophylactic insulin treatment vs placebo treatment (from 4 to 13 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
3
28
1
1
Order By: Relevance
“…In the latter, lacking functional lymphocytes, we therefore avoided the tolerizing effects of insulin on lymphocytes (Karounos et al, 1997). Figure 4 shows that prophylactic insulin treatment, administered from 3 to 6 weeks of age, decreased significantly the percentage of megaislets in NOD mice ( p ϭ 0.003), confirming previous data (Jansen et al, 1996). Moreover, it also decreased this percentage in NODscid mice to a similar extent ( p Ͻ 0.001).…”
Section: Prophylactic Insulin Treatment Prevents Mega-islet Formationsupporting
confidence: 77%
See 4 more Smart Citations
“…In the latter, lacking functional lymphocytes, we therefore avoided the tolerizing effects of insulin on lymphocytes (Karounos et al, 1997). Figure 4 shows that prophylactic insulin treatment, administered from 3 to 6 weeks of age, decreased significantly the percentage of megaislets in NOD mice ( p ϭ 0.003), confirming previous data (Jansen et al, 1996). Moreover, it also decreased this percentage in NODscid mice to a similar extent ( p Ͻ 0.001).…”
Section: Prophylactic Insulin Treatment Prevents Mega-islet Formationsupporting
confidence: 77%
“…Because insulin is known to down-regulate its own secretion (Argoud et al, 1987;Boden et al, 1993;Strubbe and Steffes, 1993) and to decrease pancreatic insulin content in NOD mice (Sai et al, 1996), we used it to prevent the transient ␤-cell hyperactivity that we previously described from 4 to 8 weeks of age in mice with the NOD genetic background (Amrani et al, 1998;Homo-Delarche, 1997). Here, we confirmed that prophylactic insulin treatment is able to reduce megaislet formation in NOD mice (Jansen et al, 1996). However, because the treatment could act on lymphocytes, via the induction of tolerance to insulin (Karounos et al, 1997), we also prophylactically treated NODscid mice, which lack functional lymphocytes.…”
Section: Insulitis and Mega-islets In Nod Micementioning
confidence: 48%
See 3 more Smart Citations